Evaluating Strategies for Teaching Micro Frontends: Do Anti-patterns Help? - Silva, Nabson; Rodrigues, Eriky; Conte, Tayana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
Context: Micro Frontend (MFE) is an architectural style that extends microservices principles to the frontend. Despite its growing adoption, misunderstandings about MFE foundations can create significant challenges during development. Preparing in-training software engineers to address these challenges and incorporating MFE into software architecture curricula is essential. Goal: We aim to address the gap in MFE education by presenting an experience report on teaching MFE in an undergraduate course. We compare two supporting materials to aid students in architectural decision-making: practitioner-provided guidelines and a catalog of MFE anti-patterns. Through a controlled experiment, we evaluate their effectiveness, with particular emphasis on understanding the role and benefits of using anti-patterns as a learning tool. Method: We taught MFE across five sessions and conducted a controlled experiment with two assessments, each one using one of the supporting materials. We compared them by analyzing differences in assessment scores and evaluated whether the catalog improved students’ perceived learning. Additionally, we investigated how students used the catalog by applying the Technology Acceptance Model and collecting qualitative feedback regarding its use. Results: Both supporting materials are equally helpful for solving MFE architectural problems. Students reported an increased perception of learning after engaging with the catalog. Their feedback indicated that the catalog was used to identify problems and solutions, promote efficient search for issues, and reinforce MFE knowledge. Conclusion: This paper provides insights into incorporating MFE into a software architecture course, proposes two supporting materials that educators can use to teach MFE, offers practical recommendations for effective instruction, and highlights the potential of the MFE anti-patterns catalog as a valuable learning tool.